The DECISIVE Study: defining beta-lactam concentration in intensive care unit patients-the pharmacokinetics of piperacillin and meropenem in critically ill patients with conserved renal function - Abdul Aziz, Mohd. Hafiz; Rozali, Mohammad Azrai; Othman Jailani, Mohd Irfan; Abd Rahman, A. N.; Sulaiman, Helmi; Atiya, N; Adiraju, S.K.S; Wallis, S.C; Wan Mat, Wan Rahiza; Mazlan, Mohd Zulfakar; Jamaluddin, M.F; Hasan, Mohd Shahnaz; et al. (Elsevier, 2020)
This was a prospective, multi-centre pharmacokinetic (PK) study conducted in three Malaysian ICUs to describe the PK of piperacillin (co-administered with tazobactam) and meropenem, and the pharmacokinetic/pharmacodynamic (PK/PD) target attainment of critically ill patients. Serial blood samples were collected to determine concentrations across seven pre-determined time-points. PK/PD target attainment was defined as a composite of: (1) the achievement of concentration 4 x the epidemiologic cut-off (ECOFF) of Pseudomonas aeruginosa and; (2) concentration below the toxicity thresholds. For piperacillin, the target concentration range was 64 – 361 mg/L and for meropenem, 8 – 64 mg/L. PK parameters were estimated using non-compartmental method. Univariate and multivariate analyses were applied. Eighty-four patients were included, 51 received piperacillin and 33 received meropenem. The most common administration method was continuous infusion (48.8%), followed by extended infusion (36.9%) and intermittent infusion (14.3%). The median (IQR) of the cohort was 58 years (42 – 69), body mass index was 23 kg/m2 (21 – 26) and the estimated Cockroft-Gault creatinine clearance (CLcr) was 62 mL/min (40 – 100). The median APACHE II and SOFA scores on admission were 13 (11 – 17) and 6 (4 – 9), respectively. Twenty-four percent of patients underwent surgery 24 hours prior to study inclusion. The volume of distribution (Vd) and CL of piperacillin were 0.42 L/kg and 0.18 L/hr/kg. The Vd and CL of meropenem were 0.37 L/kg and 0.14 L/hr/kg, respectively. Patients age, estimated CLcr and recent surgery significantly predicted the Vd and CL of both beta-lactams. Piperacillin and meropenem concentrations were highly-variable with coefficient of variation (COV) of ≥67.7%. Forty-nine patients (58.3%) achieved the PK/PD target and they tend to be older, with slower CLcr and receiving continuous infusion. Based on the most parsimonious logistic regression model, higher CLcr and intermittent infusion were significant predictors of sub-optimal PK/PD target attainment.